2011
DOI: 10.1371/journal.pntd.0001252
|View full text |Cite
|
Sign up to set email alerts
|

Secondary Buruli Ulcer Skin Lesions Emerging Several Months after Completion of Chemotherapy: Paradoxical Reaction or Evidence for Immune Protection?

Abstract: BackgroundThe neglected tropical disease Buruli ulcer (BU) caused by Mycobacterium ulcerans is an infection of the subcutaneous tissue leading to chronic ulcerative skin lesions. Histopathological features are progressive tissue necrosis, extracellular clusters of acid fast bacilli (AFB) and poor inflammatory responses at the site of infection. After the recommended eight weeks standard treatment with rifampicin and streptomycin, a reversal of the local immunosuppression caused by the macrolide toxin mycolacto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
75
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
3
2
2

Relationship

2
5

Authors

Journals

citations
Cited by 65 publications
(77 citation statements)
references
References 50 publications
(54 reference statements)
2
75
0
Order By: Relevance
“…13,14 Laboratory and radiological investigations. Baseline complete blood count, liver function test, blood urea electrolytes and creatinine, erythrocyte sedimentation rate, fasting blood sugar and sickling test with/without Hb electrophoresis as indicated were done for all patients.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…13,14 Laboratory and radiological investigations. Baseline complete blood count, liver function test, blood urea electrolytes and creatinine, erythrocyte sedimentation rate, fasting blood sugar and sickling test with/without Hb electrophoresis as indicated were done for all patients.…”
Section: Methodsmentioning
confidence: 99%
“…12 Some studies have reported paradoxical reactions in BU patients, which is defined as an increase in lesion size of 100% after initial improvement, and/or the appearance of a new lesion(s) following or during antimycobacterial treatment. 13,14 Currently, it is not clear whether immune reconstitution inflammatory syndrome (IRIS)-like mechanisms, secondary infections, 15 or other mechanisms are primarily responsible for impaired wound healing and deterioration of lesions during and after SR treatment in some of the BU patients. A retrospective study conducted in Cameroon revealed that human immunodeficiency virus (HIV) infection may affect the clinical presentation and severity of BU disease with a reported increased incidence of multiple, larger, and ulcerated BU lesions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These paradoxical reactions or inflammatory reconstitution immune syndrome (IRIS) usually, occurs 2 to 12 weeks after the initial antimicrobial treatment, although some may commence much later over 1 year after the end of treatment [12][13][14] . Clinically, lesions may seem to worsen after initial improvement, new lesions may appear, sometimes on a different part of the body, and non-ulcerative forms, such as nodules (or swelling), plaque and edema, may ulcerate.…”
Section: Bu Management In Hiv Negative Patientsmentioning
confidence: 99%
“…In HIV/TB co-infection, the incidence of TB associated IRIS in increased in those start high active antiretroviral therapy (HAART) within 30 days of commencing TB treatment [4,12] . This could be extrapolated to Bu treatment in HIV-positive to explain the occurrence of IRIS in these patients.…”
Section: Komenan K Et Al Hiv/bu Co-infection Management In Africamentioning
confidence: 99%